Taxonomic revision of the Pachycondyla apicalis species complex (Hymenoptera: Formicidae) - Wild, Alexander L. (Zootaxa, 2005)
The taxonomy of the Neotropical Pachycondyla apicalis species complex is revised. Contrary to the widely-held view that the apicalis complex contains only two species, P. apicalis (Latreille 1802) and P. obscuricornis (Emery 1890), morphological evidence indicates the existence of three broadly sympatric species. Examination of type specimens reveals that the name obscuricornis has been extensively misapplied in the literature, and that the valid name for the widespread species commonly misdiagnosed as P. obscuricornis is P. verenae (Forel 1922). True P. obscuricornis is shown to be an uncommonly collected South American species. The name apicalis is valid as currently employed for that species. A taxonomic key is provided, along with diagnoses, illustrations, and distributional data for all three species.